Noncitizen Coverage and Its Effects on U.S. Population Statistics - J. David Brown; Misty L. Heggeness; Marta Murray-Close (Institute of Labor Economics (IZA), 2023)
We produce 2020 population estimates using 31 administrative record (AR) sources. Our AR census national population estimate is 1.8% greater than the 2020 Demographic Analysis high estimate, 3.0% more than the 2020 Census count, and 3.6% higher than the vintage-2020 Population Estimates Program estimate. Inclusion of more noncitizens, especially those with unknown legal status, can explain the higher AR census estimate. About 19.8% of AR census noncitizens have addresses that cannot be linked to an address in the 2020 Census collection universe, compared to 5.7% of citizens, raising the possibility that the 2020 Census did not collect data for a significant fraction of noncitizens. We show differences in estimates by age, sex, Hispanic origin, geography, and socioeconomic characteristics symptomatic of the differences in noncitizen coverage.
Keywords: J11; J15; 330; administrative records; population estimates; immigration; noncitizen coverage